The decision to trust : how leaders create high-trust organizations - Hurley, Robert F., 1956-
A proven model to create high-performing, high-trust organizations Globally, there has been a decline in trust over the past few decades, and only a third of Americans believe they can trust the government, big business, and large institutions. In The Decision to Trust, Robert Hurley explains how this new culture of cynicism and distrust creates many problems, and why it is almost impossible to manage an organization well if its people do not trust one another. High-performing, world-class companies are almost always high-trust environments. Without this elusive, important ingredient, companies cannot attract or retain top talent. In this book, Hurley reveals a new model to measure and repair trust with colleagues managers and employees. Outlines a proven Decision to Trust Model (DTM) of ten factors that establish whether or not one party will trust the other Filled with original examples from Daimler, PriceWaterhouse Coopers, Goldman Sachs, Microsoft, QuikTrip, General Electric, Procter and Gamble, AzKoNobel, Johnson and Johnson, Whole Foods, and ZapposReveals how leaders in Asia, Europe, and North America have used the DTM to build high-trust organizations Covering trust building in teams, across functions, within organizations and across national cultures, The Decision to Trust shows how any organization can improve trust and the bottom line"--Provided by publisher.